Analisis Pengaruh Tarif Cukai Tembakau Tembakau dan Penjualan terhadap Harga Saham Perusahaan Industri Tembakau di Bursa Efek Indonesia (BEI) - Angga Pratama; Joelianti Dwi Supraptiningsih; Sopian Sopian (BADAN PENERBIT STIEPARI PRESS, 2025)
This study wants to find out how tobacco taxes and sales affect the stock prices of tobacco companies on the Indonesia Stock Exchange (IDX). It has been seen that tobacco stock prices on the Indonesia Stock Exchange have mostly gone down in the last 5 years. During this time, the government has been raising tobacco taxes, and tobacco companies' sales have been going up. This study uses a quantitative research method. Data is collected from existing sources and analyzed using the Eviews 10 program. The study found that higher &039;Tobacco Excise Rates have a negative and significant impact on stock prices. This means that when Tobacco Excise Rates go up, the stock prices of tobacco companies on the Indonesia Stock Exchange tend to go down. &039; It also found that &039;Sales have a negative and significant impact on the stock prices of tobacco companies listed on the Indonesia Stock Exchange. &039; The study hopes to give a better understanding of what affects the stock prices of tobacco companies on the Indonesia Stock Exchange..